Ten Cate's oral histology : development, structure, and function - Nanci, Antonio; Ten Cate, A. R. [ (Arnold Richard)] (Elsevier, 2013)
Understand oral histology and learn to apply your knowledge in the clinical setting with this definitive reference. Now in full color and thoroughly updated, this 8th Edition provides insight on contemporary research and trends in oral histology, embryology, physiology, oral biology, postnatal growth and development that is essential to your success in oral health! NEW! Full color format showcases vivid photomicrographs and line drawings to enhance your understanding of key oral histology learning. NEW! Chapter on facial growth and development broadens your oral histology knowledge base